Answer:
Step-by-step explanation:
so it's the total area , less the size (furniture) in the room
roomsize - furntiuresize
use the formula give for each above :)
Answer:
308 m^3
Step-by-step explanation:
The volume is given by
V = l*w*h where l is the length , w is the width and h is the height
V = 7*4*11
V = 308 m^3
Answer:
24 possible outcomes
Step-by-step explanation:
Combination has to do with selection. For example, if r object is selected from a pool of n objects, the number if possible ways can be expressed according to the combination formula:
nCr = n!/(n-r)!r!
Applying this in question, if each student receives one of 4 calculator models and one of 3 types of ruler, the number of ways this can be done is:
4C1 × 3C1
4C1 = 4!/(4-1)!1! {If a student gets one calculator)
4C1 = 4×3×2/3×2
4C1 = 4ways
3C1 = 3!/(3-2)!1! {If a student gets a ruler}
3C1 = 3×2/1
3C1 = 6ways
Total number of possible outcomes if a student gets one ruler and one calculator will be 4×6 = 24ways
Answer:
<em>Square= 12 units</em>
<em>Triangle long sides= 19 units</em>
<em>Triamgle short side= 10 units</em>
Step-by-step explanation:
<em>It is a square, so all sides are the same. That means 3x+3 equals 4x. What number can be subsituted into x to equal 4? If x is 3, then 3x+3 would be 3(3)+3. It equals 12. 4 times 3 is also 12. It works! That also means the square's side is 12 units.</em>
<em>Square= 12 units</em>
<em />
<u><em>So, x=3</em></u>
<em />
<em>The triangle's longer sides are 7x-2. Subsitute x in, which is 3, and you get 7(3)-2. It equals 19. The two longer sides of the triangle are the same length, so both are 19 units.</em>
<em>Triangle long sides= 19 units</em>
<em />
<em>The triangles shorter side is 2x+4. Subsitute 3 in for x and you get 2(3)+4. It equals 10, so the shorter side is 10 units.</em>
<em>Triangle short side= 10 units</em>
Answer: 11x + 11
Step-by-step explanation:
This is two points equation. It could be done in various ways depending on the level of understanding of the topics. The formula goes thus
y - y₁ y₂ ₋ y₁ y₂ ₋ y₁
------ = ---------- or y ₋ y₁ = --------- ˣ ( x - x₁ )
x - x₁ x₂ ₋ x₁ x₂ ₋ x₁
Where x₁ = -1, x₂ = -1, y₁ = 6, y₂ = -5. Now substitute for the values in the formula above and solve.
y - 6 -5 - 6 -11 -11
------ = -------- = ---- = -----
x - (-1) -1 - (-1) -1 + 1 0
y - 6 -11
------ = -----
x + 1 0 ,
Now we cross multiply to have a linear equation
0( y - 6 ) = -11( x + 1 )
0 = -11x - 11, now multiply by -1
The equation now becomes
11x + 11